A Concept of General Meaning: Selected Theories in Comparison to Selected Semantic and Pragmatic Theories - Kalisz, Roman (Research in Language, 2013)
The paper discusses a concept of general meaning with reference to various relevant semantic and pragmatic theories. It includes references to Slavic axiological semantics (e.g. Krzeszowski (1997); Puzynina (1992)), Wierzbicka’s (e.g. 1980, 1987) atomic expressions and classical pragmatics theories, such as speech acts, Gricean theory of conversational implicature, politeness theory and and relevance theory.